2008
DOI: 10.1508/cytologia.73.425
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Meiotic Chromosome Behaviour in Diploid Individuals of Chrysanthemum zawadskii and Related Species (Asteraceae): Evidence for Chromosome Rearrangements

Abstract: Summary Diploid individuals (2nϭ18) of Chrysanthemum zawadskii, C. indicum and C. boreale, two or all three of which often occur together in the wild in East Asia, have diverse metaphase karyotypes. We hypothesised that the diverse karyotypes result from chromosome rearrangements. To test this, we investigated chromosomal behaviour during pollen mother cell (PMC) meiosis and pollen fertility, using 33 individuals collected from seven populations in Korea. All individuals contained one or two multivalents (most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…In the species, there seems to be a direct correlation of pollen sterility with structural heterozygosity. Similar effects of structural heterozygosity resulting in non-viable pollen grains has been reported in a number of plants, namely, Chrysanthemum zawadskii (Kim et al 2008), Artemisia parviflora (Gupta et al 2010), Astragalus chlorostachys (Rana et al 2012), Saxifraga diversifolia (Kumar and Singhal 2013), Achillea millefolium (Singhal et al 2014) and Anemone rivularis (Kumar et al 2015). Gohil and Koul (1978) and Sharma and Gohil (2003) have reported that structural heterozygotes of Allium consanguineum and A. roylei depicted complete gametic sterility due to reciprocal translocations, respectively.…”
Section: Discussionsupporting
confidence: 70%
“…In the species, there seems to be a direct correlation of pollen sterility with structural heterozygosity. Similar effects of structural heterozygosity resulting in non-viable pollen grains has been reported in a number of plants, namely, Chrysanthemum zawadskii (Kim et al 2008), Artemisia parviflora (Gupta et al 2010), Astragalus chlorostachys (Rana et al 2012), Saxifraga diversifolia (Kumar and Singhal 2013), Achillea millefolium (Singhal et al 2014) and Anemone rivularis (Kumar et al 2015). Gohil and Koul (1978) and Sharma and Gohil (2003) have reported that structural heterozygotes of Allium consanguineum and A. roylei depicted complete gametic sterility due to reciprocal translocations, respectively.…”
Section: Discussionsupporting
confidence: 70%
“…In the presently studied accession of Tanacetum artemisioides, the majority of the PMCs showed the adjacent type of orientation of quadrivalents/hexavalents (ring or chain) and the alternate (zigzag) orientation was seen in only one PMC, resulting in a considerable amount of pollen sterility (30-35%), which appears to be the result of duplications and deficiencies of genes as mentioned by Ghosh and Datta (2006) in Nigella damascene. Similar effects of structural heterozygosity leading to nonviable pollen grains have been reported in a number of plants, namely, Citrus jambhiri (Singhal and Gill 1981), Chrysanthemum zawadskii (Kim et al 2008), Artemisia parviflora (Gupta et al 2010), Astragalus chlorostachys (Rana et al 2012), Saxifraga diversifolia (Kumar and Singhal 2013), Tradescantia spathacea (Koul et al 2013), Achillea millefolium (Singhal et al 2014), and Anemone rivularis (Kumar et al 2015). Gohil and Koul (1978) and Sharma and Gohil (2003) have reported that structural heterozygotes of Allium consanguineum and A. roylei depict complete gametic sterility due to reciprocal translocations.…”
Section: Discussionsupporting
confidence: 55%
“…Ever since the first report of structural heterozygosity for reciprocal translocations by Belling (1914) in Florida velvet bean (Stizolobium deeriingianum), heterozygosity has been reported to occur in a wide variety of flowering plants (Burnham 1956, Kaul 1977, Gohil and Koul 1978, Sharma and Gohil 2003, Talukdar and Biswas 2006, Kim et al 2008, Ghaffari et al 2009, Talukdar 2010, 2013, Kohli and Gohil 2011. From this laboratory, the naturally occurring reciprocal translocations have been reported in individuals of Artimisia parviflora (Gupta et al 2010), Astragalus chlorostachys (Rana et al 2012), Saxifraga diversifolia (Kumar and Singhal 2013), Achillea millefolium (Singhal et al 2014), and Anemone rivularis (Kumar et al 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Two C. zawadskii (one from each population) and two C. indicum (both from Kwangha-ri) were used for an intensive study of PMC meiosis. One of the two C. indicum had atypical white heads, as in C. zawadskii, thus appearing to be a hybrid between C. zawadskii and C. indicum (Kim et al 2008). Eighteen C. zawadskii, nine from each population, and nine typical and nine atypical C. indicum were used to confirm that syncyte formation occurs extensively in these species.…”
Section: Plant Materialsmentioning
confidence: 99%